Adaptive Memory of Human NK-like CD8+ T-Cells to Aging, and Viral and Tumor Antigens - Pita-López, María Luisa; Pera, Alejandra; Solana, Rafael (Frontiers in Immunology, 2016)
Human natural killer (NK)-like CD8+ T-cells are singular T-cells that express both T and NK cell markers such as CD56; their frequencies depend on their differentiation and activation during their lifetime. There is evidence of the presence of these innate CD8+ T-cells in the human umbilical cord, highlighting the necessity of investigating whether the NK-like CD8+ T-cells arise in the early stages of life (gestation). Based on the presence of cell surface markers, these cells have also been referred to as CD8+KIR+ T-cells, innate CD8+ T-cells, CD8+CD28−KIR+ T-cells or NKT-like CD8+CD56+ cells. However, the functional and co-signaling significance of these NK cell receptors on NK-like CD8+ T-cells is less clear. Also, the diverse array of costimulatory and co-inhibitory receptors are spatially and temporally regulated and may have distinct overlapping functions on NK-like CD8+ T-cell priming, activation, differentiation, and memory responses associated with different cell phenotypes. Currently, there is no consensus regarding the functional properties and phenotypic characterization of human NK-like CD8+ T-cells. Environmental factors, such as aging, autoimmunity, inflammation, viral antigen re-exposure, or the presence of persistent tumor antigens have been shown to allow differentiation (“adaptation”) of the NK-like CD8+ T-cells; the elucidation of this differentiation process and a greater understanding of the characteristics of these cells could be important for their eventual in potential therapeutic applications aimed at improving protective immunity. This review will attempt to elucidate an understanding of the characteristics of these cells with the goal toward their eventual use in potential therapeutic applications aimed at improving protective immunity.